2012
DOI: 10.1680/geot.8.p.084
|View full text |Cite
|
Sign up to set email alerts
|

Parameters controlling stiffness and strength of artificially cemented soils

Abstract: The treatment of soils with cement is an attractive technique when a project requires improvement of the local soil for the construction of subgrades for rail tracks, for roads, as a support layer for shallow foundations, and to prevent sand liquefaction. This paper advances understanding of the key parameters for the control of strength and stiffness of cemented soils by testing two soils with different gradings and quantifying the influence of porosity/cement ratio on both initial shear modulus (G 0 ) and un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(42 citation statements)
references
References 10 publications
(9 reference statements)
2
35
0
5
Order By: Relevance
“…The results of unconfined compression strength and maximum shear modulus presented in this paper showed that the best exponent to the fine sand fraction is 0?10, while for Osorio sand it is 1?0 (Consoli et al, 2012a), despite their close grain size distribution curves. Again, this can be explained by their different mineralogies, which result in different particle shapes.…”
Section: Resultsmentioning
confidence: 65%
See 2 more Smart Citations
“…The results of unconfined compression strength and maximum shear modulus presented in this paper showed that the best exponent to the fine sand fraction is 0?10, while for Osorio sand it is 1?0 (Consoli et al, 2012a), despite their close grain size distribution curves. Again, this can be explained by their different mineralogies, which result in different particle shapes.…”
Section: Resultsmentioning
confidence: 65%
“…According to Consoli et al (2012a), mineralogical analysis of this soil showed that the sand particles are predominantly quartz.…”
Section: Grain Size Distribution and Mineralogymentioning
confidence: 95%
See 1 more Smart Citation
“…Natural cementing agents include calcium carbonate and precipitated salts (Mitchell and Soga 2005), whereas artificial cementation with Portland cement has been used for soil stabilization (PCA 2003). Numerous studies describe the role of cementation on small-strain dynamic properties (e.g., Baig et al 1997) and strength behavior (e.g., Clough et al 1981;Lade and Overton 1989;Consoli et al 2012) of sands. In general, the role of mineral-based cementation on strength and stiffness is stress-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The most common additive is Portland cement, and is typically incorporated in the soil by mixing (e.g., Consoli et al 2012). Recent work on bio-cementation relies on calcium carbonate deposited in the soil via bacterial action (DeJong et al 2010).…”
Section: Introductionmentioning
confidence: 99%